PENGARUH KINERJA TENAGA ADMINISTRASI SEKOLAH TERHADAP KUALITAS LAYANAN ADMINISTRASI NON AKADEMIK - admin admin; Rufqotuz Zakhiroh (Universitas Muhammadiyah Gresik, 2013)
School as a public institution should be able to satisfy their customers. The paradigm of public services in the unit level of education should be shifted from conventional towards the continuously updated condition so that when it is needed it will be ready to provide services (on-service). The administrative staff of school should represent as a public servant who is pro-active, responsive and anticipative to the needs, aspirations and expectations of school stakeholders in accordance to Permendiknas No. 24 of 2008 on Standards of School Administration Staff. Therefore, in addition to mastery a variety of hard skills, which include technical skills, school administrative staff also must be a master of variety of soft skills which are always displayed at the time of providing services to create the customers' satisfaction.